Quantitative risk analysis on an FSO crude oil storage tank / Siti Rafidah Ab Rashi and Adil Rahman Nor Azmi - Ab Rashi, Siti Rafidah; Nor Azmi, Adil Rahman (Universiti Teknologi MARA, 2020)
The industry of oil and gas are blooming in a rapid rate as time goes by because of the massive use of fuel oil and natural gas in this age of time. However, as more fuel oil are produced the industry is moving away from onshore to offshore and towards the ultra-deepwater region, where vessel like FSOs are introduced. FSO are short for Floating Storage and Offloading which are vessels used in deep water operation. The FSO plays an important role in the business where a single disastrous incident will affect the industry and the company. The focus of the research will be on the FSO that holds million barrels of crude oil. In this work, fire risk analysis is used to assess the crude oil storage tank on a typical FSO as this is a relatively new mode in exploration and production (E&P) activity. By calculating the individual risk per annum (IRPA) and potential loss of life (PLL), methods are introduced to mitigate fire risk on FSOs. The results show that the level of failure is low and requires less action for the FSO crude oil storage tank to stay safe duringoperation in the offshore environment.